Genetic relatedness in Monk Parakeet breeding trios - Bucher, Enrique Hugo (2016)
Monk Parakeets (Myiopsittamonachus) are cooperative breeders, which means that one adult helps the breedingpair (trios). We found a breeding trio composed of two males and one female ina single breeding chamber of a two-chamber compound nest. Males were fullsiblings.. The female was the halfsibling of both males. The female and one male were genetic parents of allnestlings. The sampled parakeet population showed a higher than expected levelof inbreeding. The Monk Parakeet provides an interesting model forunderstanding of the role and benefits of helping and extra parental behaviorin cooperative breeding birds.